Optimización de parámetros para la obtención de micropartículas a base de extracto de huasaí (Euterpe precatoria Mart.) por Spray drying - Yuyarima Mashingashi, Leny Mercedes (2025)
Huasaí (Euterpe precatoria) is an Amazonian fruit that contains a variety of bioactive compounds with antioxidant effects in our body, improving health. However, this fruit perishes shortly after harvest, causing the loss of many secondary metabolites present in huasaí fruit. Therefore, this research work was developed with the objective of optimizing the parameters for obtaining microparticles of huasaí extract by spray drying, aiming to achieve optimal microencapsulation conditions. The encapsulating agents used were maltodextrin and gum Arabic, with which the microencapsulation process was optimized, providing desirable values for the dependent variables. The Response Surface Methodology (RSM) with a central composite design, Box Wilson, was used for the optimization process. This allowed us to evaluate the influence of the independent variables, temperature (125–145 ºC) (X1) and polymer ratio (GA:MD) (X2) at 8%, on the responses: yield (R’), solubility (S’), hygroscopicity (H’), and antioxidant capacity measured by ABTS and DPPH assays. The optimal values obtained were 77.47±4.10%; 94.29±0.74%; 3.06±0.22%; 67.57 mg/100g; 2803.28±12.38 mg GAE/g DW; 18490.50±49.18 µmol TE/g DW; 7183.12±40.23 µmol TE/g DW. In conclusion, the optimization process of microencapsulation of whole pulp huasaí extract using gum Arabic and maltodextrin yielded microparticles with a high content of bioactive compounds, high solubility index, and low moisture and hygroscopicity. It is noteworthy that maltodextrin combined with gum Arabic proved more effective than using gum Arabic alone.